Screening of the factors for novel pour point depressant copolymer synthesis to improve the copolymer yield - B S, Elarbe; N., Ridzuan; K., Yusoh; Ibrahim, Elganidi; N, Abdullah (IOP Publishing, 2019)
Pour point depressants (PPDs) commonly used in the oil and gas industry as a chemical wax inhibitor to control the temperature of the crude oil below their wax appearance temperature (WAT) points, and to improve the flowability of crude oil. In this study, different conditions of Stearyl Acrylate-Behenyl Acrylate (SABA) copolymer were synthesized by freeradical solution polymerization method at different range conditions of polymerization. Four factors considered during the synthesize of the copolymer are the mass ratio of monomers (1:1,1:2, 1:3, 2:1, and 3:1 wt%), reaction temperature from 60 to 100 °C, the concentration of initiator from 0.5 to 2.5 wt% and reaction time from 5 to 9 hour. The results showed that the best conditions to obtain the highest yield of SABA copolymer were at the mass ratio of monomers of 1:1 (w/w), the reaction temperature of 90 ºC, the reaction time of 7 h, and concentration of initiator at 1 wt%.